Africa and Urban Anthropology Theoretical and Methodological Contributions from Contemporary Fieldwork - Pellow, Deborah; Scheld, Suzanne (Routledge Studies in Anthropology, 2023)
This volume offers valuable anthropological insight into urban Africa, covering a range of cities across a continent that has become one of the fastest urbanizing geographic areas of the globe. Consideration is given to the structures, social formations, and rhythms that constitute the definition of an African city, town, or urban space, and to current concepts for thinking about African cities in the twenty-first century. The contributors examine topics including notions of belonging, the effects of globalization, colonialism, and transnationalism on African urban life, the cultural dimensions of infrastructure and public resources, mobility, labor issues, spatial organization, language, and popular culture trends, among other themes. The book reflects on how the ethnography of urban Africa fits within anthropology and urban studies, and on new theoretical concepts and methodologies that can be created through anthropological fieldwork in African cities. It will be of particular interest to scholars and students from anthropology, African studies and urban studies, as well as sociology and geography.